Evaluasi Penerapan Teknik Supervisi Pendidikan di Madrasah Aliyah (MA) Al-Hamidy Banyuanyar Pamekasan - Rahman, Kholilur; Zahroh, Ifqotus; Nurhadi, Ali (Al-Qiyadi Jurnal Manajmen Pendidikan Islam, 2025)
This study aims to evaluate the implementation of educational supervisiontechniques at Madrasah Aliyah (MA) Al-Hamidy Banyuanyar Pamekasan. Theinstitution is known to apply three main supervision techniques in conductingacademic and professional development for teachers. The research employs aqualitative approach with an exploratory design. Data were collected throughobservation, interviews, and documentation to obtain a comprehensiveunderstanding of the supervision practices within the madrasah. Data analysisrefers to Alfonso’s theory, which highlights three behavioral systems ofeducational supervision: academic supervisory behavior, teachers’ academicbehavior, and students’ learning behavior. The findings show that theimplementation of educational supervision at MA Al-Hamidy has had a positiveimpact on improving the quality of learning. First, academic supervisory behaviorshows improvement in planning, implementation, and follow-up supervision.Second, teachers’ academic behavior has undergone significant changes in termsof discipline, creativity, and pedagogical competence. Third, students’ learningbehavior has also improved, including motivation, participation, and learningoutcomes.